ASEAN’s Role in Shaping Nuclear Security Future in the Region - Mutti Anggitta (JAS (Journal of ASEAN Studies), 2016)
The objective of this essay is to discuss the potential future of nuclear security in Southeast Asia by examining the roles of the Association of Southeast Asian Nations (ASEAN) in establishing and maintaining regional cooperation on nuclear security. This essay will first outline nuclear renaissance and security challenges in the region. It will then discuss the steps that have been taken and could be taken by ASEAN to lead the region to a safer nuclear security future.